PERSONALITY COMPETENCE OF EDUCATORS TO SA'ID HAWWA PERSPECTIVE - Junaidi Arsyad; Azizah Hanum OK; Rudi Saputra (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
Personality is the element that determines the interaction of educators with students as role models, educators must have personalities that can be used as profiles and idols. To examine the personality of educators, it is necessary to examine the previous scholars, because it is undeniable that there are not a few contributions given by the previous scholars, especially in the world of education, one of which is Sa'id Hawwa. The objectives of this research are. 1) To analyze the personality competencies of educators according to Sa'id Hawwa. 2) To analyze the relevance of the personality competencies of educators according to Sa'id Hawwa with contemporary Islamic education. In this research, the approach used is a qualitative approach with the type of character study research with two stages, namely inventory and critical evaluation. The data collection instrument in this study was documentation in the form of books by Sa'id Hawwa related to this research. The results show that 1) The personality competencies of educators according to Sa'id Hawwa are understanding, sincere, guiding the community, jihad/sincere, willing to sacrifice, obedient, consistent, brotherly/ukhuwah, honest, committed and intelligent. 2) The relevance of the personality competencies of educators according to Sa'id Hawwa with contemporary Islamic education is appropriate, even though the personality competencies of educators are contained in the Law on Educators and Lecturers No. 14 of 2005 which is intended for the public and decided nationally and is not based on Islam, but contains very Islamic values